Entire multivariate vector-valued functions of bounded $L$-index: analog of Fricke’s theorem - A. I. Bandura; V. P. Baksa (Математичні Студії)
We consider a class of vector-valued entire functions $F\colon \mathbb{C}^{n}→ \mathbb{C}^{p}$. For this class of functions there is introduced a concept of boundedness of $L$-index in joint variables.